Short- and long-term results for severe hallux valgus correction using a first metatarsal distal osteotomy. Issue 8 (December 2022) - Ledermann, Gerardo; Baduell, Albert; Testa, Enrique; Vega, Ricardo; Ruiz, Pablo; Barrientos, Miguel; Poggio, Daniel
Abstract: Purpose: The purpose of this study is to analyze the short- and long-term results of severe hallux valgus (HV) treated with a L -Reverse osteotomy. Methods: Patients treated with L -Reverse osteotomy for severe HV between the years 2006–2015 were included. Patients were evaluated preoperatively, at 3 months and 4 or more years postoperatively. Changes in the HV angle (HVA) and intermetatarsal angle (IMA) were measured. Clinical outcomes were assessed using the AOFAS score. Results: 28 patients were included. Pre-operative IMA changed from 18.1° (18–18.9°) to 7° (6.3–8.5°), and HVA from 38.5° (34.5–41.3°) to 10.0° (8.4–11.8°) at 3 month follow up (p < 0.005). Long term follow up was of 5.6 (4.9–6.4) years. IMA value was 7.5° (6.1°−8.1°) and HVA was 10.1° (6.7°−16.3°), with no statistical difference with initial correction (p = 0.14). Median AOFAS score was 92.7 (89–4–96.1). Conclusion: L -Reverse osteotomy can achieve correction of HV severe deformities with good outcomes in long term follow up. Level of evidence: III